Weeds in Second Corn Crops in the Period of Transgenic Soybean Implantation in the Middle Paranapanema Region - HIRATA,A.C.S. (2018)
ABSTRACT: The Middle Paranapanema region concentrates a large part of the second corn production in São Paulo State. Weed surveys in commercial areas are important for monitoring and directing their management. In 2006, 2007, and 2008, weed surveys were carried out on 27, 25, and 24 corn crops, respectively, in ten counties of this region. At the grain filling stage, crops were zigzag sampled with 20 points of 1 m2 per area. In addition, information on weed management, soil cover, and history of the summer crop were collected. The phytosociological parameters frequency, density, abundance, and importance value index were determined. The results evidenced Cenchrus echinathus as the most important species in 2006 and 2007, in addition to high importance values in 2008, which reflected the need to improve its management. Bidens pilosa, Digitaria horizontalis, and Euphorbia heterophylla were important species for the crop. Although under a low frequency, outbreaks of Leonurus sibiricus and Gnaphalium spicatum were observed in the areas, increasing their importance in 2007 and 2008. Atrazine was the most used herbicide over the agricultural years, with a low use of other products. Soil cover presented a high variation, but a high number of fields presented a low soil cover. Despite the increase of transgenic soybean in this region, no consistent evidence of changes in weed community resulted from this transition.